Prediction of the development of postoperative pain in patients with late-stage knee osteoarthritis based on the expression of genes for degradation of the extracellular matrix, inflammation and apoptosis in the blood - E. V. Chetina; K. E. Glemba; G. A. Markova; E. A. Naryshkin; E. A. Taskina; M. A. Makarov; A. M. Lila (Современная ревматология, 2022)
About 10–40% of patients with osteoarthritis (OA) are not satisfied with the results of total arthroplasty (TA) of large joints. At the same time, the most common complication associated with the ineffectiveness of TA is postoperative pain (PP).Objective: to identify genes whose expression in the peripheral blood before TA is associated with an increased risk of PP developing. Patients and methods. Before TA, the blood of 50 patients with late-stage knee OA was examined; the control group consisted of 26 healthy individuals. The level of pain was assessed using the visual analog scale (VAS), the BPI short questionnaire, and the WOMAC index; the presence of neuropathic pain was assessed using the DN4 and PainDETECT questionnaires. The development of PP was determined 3 and 6 months after TA. The levels of matrix metalloproteinase protein (MMP) 9 and tissue inhibitor of metalloproteinase (TIMP) 1 were quantified by ELISA. Total RNA isolated from blood was used to determine the expression of caspase 3, MMP9, TIMP1, cathepsins K and S, tumor necrosis factor (TNF) α, interleukin (IL) 1β, and cyclooxygenase 2 genes using a quantitative real-time reverse transcriptase polymerase chain reaction.Results and discussion. PP according to VAS ≥30 mm was noted in 17 patients. Before TA, these patients had significantly increased expression of cathepsins K and S, caspase 3, TIMP1, IL1β, and TNFα genes compared to other patients with OA. ROC analysis revealed a statistically significant relationship between the expression of these genes and the likelihood of developing pain after TA.Conclusion. High expression of genes associated with degradation of the extracellular matrix (catepsins S and K, TIMP1), inflammation (IL1β, TNFα), and apoptosis (caspase 3) can serve as an important biomarker for the development of PP in patients with knee OA. To confirm the value of preoperative gene expression testing in predicting the onset of PP, further studies involving large cohorts of patients are needed.